Controlled Nucleation of Graphene Domains on Copper With an Oxide Layer by Atmospheric Pressure Chemical Vapor Deposition - Zhang, Rujing; He, Limin; Zhen, Zhen; Xu, Zhenhua; Li, Na; Zhu, Hongwei (Frontiers in Materials, 2019)
The lack of effective control on the defects and layers of graphene restricts its advanced technological applications. The synthesis of high-quality graphene requires a low nucleation density. By the pre-oxidation of copper foil and subsequent annealing in reducing atmosphere with different time, the effect of surface morphology variation on the nucleation density of graphene domains were discussed, as well as on the domain size. The obtained domain is the combination of sub-millimeter-size single-crystal graphene layer and thick multilayer graphene branches. The formation mechanism of the special structure was explored, as the accumulation of carbon atoms at the surface impurities with the help of oxygen. These results provide directions for the synthesis of controllable high-quality graphene films.